Unipolar resistive switching in metal oxide/organic semiconductor non-volatile memories as a critical phenomenon - Bory, Benjamin F. (2018)
Diodes incorporating a bilayer of an organic semiconductor and a wide bandgap metal oxide can show unipolar, non-volatile memory behavior after electroforming. The prolonged bias voltage stress induces defects in the metal oxide with an areal density exceeding 10(17) m(-2). We explain the electrical bistability by the coexistence of two thermodynamically stable phases at the interface between an organic semiconductor and metal oxide. One phase contains mainly ionized defects and has a low work function, while the other phase has mainly neutral defects and a high work function. In the diodes, domains of the phase with a low work function constitute current filaments. The phase composition and critical temperature are derived from a 2D Ising model as a function of chemical potential. The model predicts filamentary conduction exhibiting a negative differential resistance and nonvolatile memory behavior. The model is expected to be generally applicable to any bilayer system that shows unipolar resistive switching. (C) 2015 Author(s).